Magma oceans, iron and chromium redox, and the origin of comparatively oxidized planetary mantles. (1st July 2022) - Hirschmann, M.M.
Abstract: The mantles of both Earth and Mars are more oxidized than would be expected based on low pressure equilibration of molten silicate and alloy during their magma ocean stages. High pressure silicate-alloy equilibration in a magma ocean can produce appreciable ferric iron in the silicate, leading to comparatively oxidized near surface conditions and overlying atmospheres. Upon crystallization, this may feasibly be sufficient to account for oxygen fugacities prevailing in basalt source regions of Earth and Mars. Experiments and first principles studies affirm that Fe 3+ is stabilized at high pressure, but to date there has been no model that accounts accurately for the combined effects of melt composition, temperature, pressure, and oxygen fugacity on magma ocean Fe 3+ /Fe T . We calibrate a new model for Fe 3+ /Fe T as a function of temperature, pressure, melt composition, and f O2 which reproduces Fe 3+ /Fe T for experimental peridotite liquids and which incorporates differences in FeO and Fe2 O3 liquid heat capacities into a potentially realistic temperature function. For the effects of pressure, two versions of the model are implemented based on recent equations of state (EOS), though only the EOS of Deng et al. (2020) is applicable to pressures relevant to metal-silicate equilibration in a deep terrestrial magma ocean. For Earth, metal-silicate equilibration at 28–53 GPa, 2300–4100 K, and f O2 set by plausible mantle and core compositions produces Fe 3+ /Fe T between 0.034 and 0.10, with variation mostly owing to differences in assumed temperatures. For Mars, different proposed mantle compositions produce Fe 3+ /Fe T ratios that range from 0.026 for FeO* of 13.5 wt.% up to 0.038 for FeO* of 18.1 wt.%. Although significant Fe 3+ may be present in magma oceans owing to high pressure equilibration with alloy, the budget of Fe2 O3 in crystallized mantles is expected to be modified from that in the molten state. An important additional factor is the influence of Cr, which is Cr 2+ in molten silicate equilibrated with alloy and Cr 3+ in terrestrial upper mantles. Production of Cr 3+ and Fe 2+ by reaction with Cr 2+ and Fe 3+ during crystallization can destroy much of the Fe2 O3 present during the magma ocean stage. Considering the stability of Cr 2+ in olivine and the temperature-dependent partitioning of Cr 3+ between mantle silicates, we construct an empirical model for the fraction of Cr that is Cr2 O3 in solid spinel peridotite as a function of temperature and f O2 . For Earth, at least 0.35 wt.% Fe2 O3 is destroyed by oxidation of magma ocean CrO and for Mars, more than 0.55 wt.% Fe2 O3 should be destroyed. Consequently, either the terrestrial and martian magma oceans were significantly more enriched in Fe2 O3 than their present-day upper mantles or other processes contributed to oxidation of the latter. Over-enrichment of Fe2 O3 in the magma oceans is plausible only if terrestrial metal-silicate equilibration occurred above 3300 K and if the martian mantle contains >17 wt.% FeO*. Subsolidus disproportionation of ferrous iron may have contributed to the present-day redox state of the Earth's mantle, and late accretion of chondrite-like material and hydrogen degassing also likely affected the solidified mantles of both Earth and Mars.